2020
DOI: 10.3171/2020.5.jns20577
|View full text |Cite
|
Sign up to set email alerts
|

Fellowship, gender, and scholarly productivity: trends among academic neurosurgeons in the US

Abstract: OBJECTIVECurrent data on fellowship choice and completion by neurosurgical residents are limited, especially in relation to gender, scholarly productivity, and career progression. The objective of this study was to determine gender differences in the selection of fellowship training and subsequent scholarly productivity and career progression.METHODSThe authors conducted a quantitative analysis of the fellowship training information of practicing US academic neurosurgeons. Information was extracted from public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Additionally, men had higher scholarly productivity in every subspecialty of neurosurgery despite proportionally more females completing neurosurgical fellowships and having similar or higher levels of research output later in their careers. 22 Within other specialties, such as otolaryngology, male PIs were found to have higher average NIH funding totals compared to female PIs, even when adjusted for academic rank and active years. 23 Men also tended to receive more prestigious grants or grants with more funding compared to women in several specialties.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, men had higher scholarly productivity in every subspecialty of neurosurgery despite proportionally more females completing neurosurgical fellowships and having similar or higher levels of research output later in their careers. 22 Within other specialties, such as otolaryngology, male PIs were found to have higher average NIH funding totals compared to female PIs, even when adjusted for academic rank and active years. 23 Men also tended to receive more prestigious grants or grants with more funding compared to women in several specialties.…”
Section: Discussionmentioning
confidence: 96%
“…20 In addition, researchers found that females had an overall lower H-index in every neurosurgical subspecialty, despite having higher rates of fellowship completion. 15 However, in reporting these differences in H-indices and additional graduate degrees, we cannot make a truly objective statement about these trends given that we were not able to control for length of practice or age of the individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This trend may not be surprising as recent studies have found that significant barriers exist for females, especially in research productivity and academia. [13][14][15] Even though there was a significant increase in female first authorship for neurosurgery journals between 2013 and 2018, there was no increase in senior authorship, and there were significantly fewer publications by females than males overall. 13 This decreased productivity also manifests in neurological research conferences, where females constituted a minority of speakers from 2014 to 2018 and were generally underrepresented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Furthermore, despite the fact that women had increased fellowship completion over their male counterparts, women still had lower scholarly productivity. 27 Mentorship, as described in this study, is to be distinguished from sponsorship. Sponsorship is the use of one's own advanced status to advocate for the advancements and opportunities for the mentee.…”
Section: Implications Of Findingsmentioning
confidence: 99%